2018
DOI: 10.1523/jneurosci.3152-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dimensional and Monotonic Preparatory Activity in Mouse Anterior Lateral Motor Cortex

Abstract: Neurons in multiple brain regions fire trains of action potentials anticipating specific movements, but this "preparatory activity" has not been systematically compared across behavioral tasks. We compared preparatory activity in auditory and tactile delayed-response tasks in male mice. Skilled, directional licking was the motor output. The anterior lateral motor cortex (ALM) is necessary for motor planning in both tasks. Multiple features of ALM preparatory activity during the delay epoch were similar across … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 67 publications
8
88
0
Order By: Relevance
“…What could be the cause of these differences? Spike rates in individual ALM neurons often increase or decrease during a trial in ramp-like patterns[ 25 , 34 , 45 ]. Right-preferring selectivity was more often associated with neurons ramping up on right trials, whereas left-preferring selectivity included many neurons with firing rates ramping down in the non-preferred ('right') trial ( Fig 2J ).…”
Section: Resultsmentioning
confidence: 99%
“…What could be the cause of these differences? Spike rates in individual ALM neurons often increase or decrease during a trial in ramp-like patterns[ 25 , 34 , 45 ]. Right-preferring selectivity was more often associated with neurons ramping up on right trials, whereas left-preferring selectivity included many neurons with firing rates ramping down in the non-preferred ('right') trial ( Fig 2J ).…”
Section: Resultsmentioning
confidence: 99%
“…Actions may be generated by an inherently noisy system: synapses are unreliable ( Allen and Stevens, 1994 ), neurons generate variable spike trains ( Mainen and Sejnowski, 1995 ), and neural circuits may operate near the edge of chaos ( van Vreeswijk and Sompolinsky, 1996 ). On the other hand, neural networks, whether adaptive or hard-wired, have structures that shape population neural dynamics onto a low dimensional manifold, where nonrandom and ordered activity patterns emerge ( Ganguli et al, 2008 ; Harvey et al, 2012 ; Inagaki et al, 2018 ). Computational models have promised to provide a unified view of these observations ( Burak and Fiete, 2012 ; Brennan and Proekt, 2019 ; Mastrogiuseppe and Ostojic, 2018 ; Roberts et al, 2016 ), but a deep connection between theories and experiments remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…These elaborate behavioral computations manifest in complex neural dynamics, and occur across multiple temporal scales and brain areas 111 . For example, recent studies in mice identified anterior lateral motor (ALM) cortex as a critical circuit node for perceptual decision tasks 912 . ALM neurons exhibit complex, heterogeneous, epoch-dependent dynamics; population dynamics in ALM and connected thalamic nuclei 13 evolve over time scales of milliseconds to seconds.…”
Section: Introductionmentioning
confidence: 99%